ケイタイ ヨウ コウゴウセイ ソクテイ ソウチ ヲ モチイタ ナンキョク ラングホブデ デノ センルイ ノ コウゴウセイ ノ ソクテイ - 伊野, 良夫; イノ, ヨシオ; Ino, Yoshio (1994)
P(論文) 南極に生育する植物の一次生産量を計算するためや, 蘚類・地衣類の環境適応を調べるために, 光合成の測定がなされてきたが, その例は少ない。この測定には多くの計器, 機材が必要とされ, それが南極での測定が少ない原因と考えられる。近年, 数種の携帯用の光合成・蒸散測定装置が発売された(例えば, The Analytical Development社, LI-COR社, Warz社)が, これらはいずれも葉を挾んで, その二酸化炭素の取り込みを測定するものであり, 蘚類・地衣類には用いることができなかった。9cmシャーレが入る小型同化箱を開発し, 測定装置(小糸製作所, KIP9000)をそれにあわせて改良し, 東南極のラングホブデ雪鳥沢で, 2種の蘚類の光合成と暗呼吸速度を測定した。サンプル1(Bryum pseudotriquetrumとCeratodon purpureusの混生したもの)で約9時間, サンプル2 (C. purpureus)で約11時間の連続測定を行った。呼吸速度が大変大きく, そのため光補償点はかなり高かった。この装置で得られた結果は, 同時期に同じ場所で使用した大型の測定装置(分析部 : 堀場製作所VIA-300,同化箱 : 小糸製作所MC-A3W)で得られた結果(Y. INO : Ecol. Res., 5,195,1990)とほぼ同じであった。ただし, 最大光合成速度は若干高かった。 The photosynthesis of mosses was measured with a portable CO_2 porometer (modified Koito KIP9000) at Langhovde, East Antarctica in January 1988. An assimilation chamber, 10cm×10cm×6.5cm, which was made for this measurement, was used in collecting data for 9h in Sample 1 and 11h in Sample 2. Samples were mixed communities of Bryum pseudotriquetrum and Ceratodon purpureus (Sample 1) and C. purpureus (Sample 2) collected in the Yukidori Valley, Langhovde. Both samples had high respiration rates. Net photosynthetic rates were negative at low irradiance and changed to positive rates at high irradiance. Maximum photosynthetic rates were higher than those of other mosses measured with other equipment (analyzer : Horiba VIA-300,assimilation chamber : Koito MC-A3W) in the Yukidori Valley in the same period (Y. INO : Ecol. Res., 5,195,1990) departmental bulletin paper